2016
DOI: 10.1155/2016/8542147
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Health-Related Quality of Life and Its Predicting Factors in the Postpartum Period in Iran

Abstract: Background/Purpose. Postpartum period is accompanied by many physical, emotional, and social changes in women's health. The aim of this study was to examine the mothers' quality of life in postpartum period. In addition, it also sought to recognize the variables that predict their quality of life. Methods. This cross-sectional, descriptive study was undertaken among 380 women in 10 urban health centers in Ilam province in west of Iran. They were selected using proportional random sampling method. The SF-36 que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
49
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 24 publications
10
49
3
Order By: Relevance
“…Furthermore, [19], demonstrated that, the difference between vaginal delivery and CS section was highly significant in terms of mean score of QoL in the postpartum period. This result was not in agreement with [20] who displayed that, there were no differences between postpartum QoL of women after vaginal and caesarean delivery.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Furthermore, [19], demonstrated that, the difference between vaginal delivery and CS section was highly significant in terms of mean score of QoL in the postpartum period. This result was not in agreement with [20] who displayed that, there were no differences between postpartum QoL of women after vaginal and caesarean delivery.…”
Section: Discussioncontrasting
confidence: 76%
“…Similarly, [21] who found that in Dezful, Iran, they found that the income is an important factor for better QoL. But, [20] stated that, there was no difference between women QoL and their incomes. This can be due to their tending to not expose their real financial situation.…”
Section: Discussionmentioning
confidence: 97%
“…Women's demographic data included age, educational level, employment status, health insurance status, and relationship status . Age was categorized into three groups: ≤30, 31‐35, and ≥36 years.…”
Section: Methodsmentioning
confidence: 99%
“…Women's demographic data included age, educational level, employment status, health insurance status, and relationship status. [19][20][21][22] Age was categorized into three groups: ≤30, 31-35, and ≥36 years. Educational level was categorized as secondary education or lower, third-level nondegree (National Certificate or Diploma)/third-level primary degree (Bachelor), postgraduate certificate, or diploma/postgraduate degree (Masters)/PhD.…”
Section: Data Collection On Sociodemographic and Clinical Charactermentioning
confidence: 99%
“…However, given the impact and risk on postpartum mothers, it is not surprising that the quality of life of the mother can decrease. The main reason for the decline in the quality of life of postpartum mothers is that women have physical, psychological and social problems during this period (Rezaei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%